The importance of the one man’s company under the new Saudi Companies Law 2015 - Dr. Maen Mohammed Amin Ali Alqudah (مجلة العلوم الشرعية, 2019)
Key Words New Saudi Company Law, One man’s company, commercial companies, Persons Companies, the Joint-Stock Company, limited liability Company, partners, financial disclosure, founder, Board of Directors. Abstract: The companies’ role is highly significant in the economic and trade development. In this sense, countries are seeking to take into consideration to organize the companies’ type, legal forms and the rules of their foundation procedure. In addition, the legal doctrine classified the type of commercial companies into: persons Company, the Joint-Stock Company and mixed companies (between persons and the joint-stock companies). However, due to the rapid commercial growth, economic sectors, and the vital need to cope with this growth, another type of companies differs from the traditional classification of commercial companies, which has become known as one man’s company. In this context, the new Saudi Company Law 2015 emphasizes that one man’s company should be established. One man’s company arises several questions that will be addressed in this paper: is it a necessity finding such a company under the new Saudi Companies Law 2015? Are the legal provisions appropriate and sufficient to handle this type of company? Is it important to impose regulations regarding this company in the absence of an independent legal regulation of this type of company?